Using distribution and movement of invasive channel catfish Ictalurus punctatus in the San Juan River to inform removal efforts - Epping, Keegan C. (My University, 2025)
The invasion of nonnative fishes has homogenized regionally endemic communities with species in the American West being disproportional impacted. In the San Juan River, New Mexico, Colorado, and Utah, invasive channel catfish Ictalurus punctatus may harm the native fish community through predation and competition. Because of this perceived threat, a removal program was implemented in the 1990s; however, exploitation rates have suggested that these efforts were insufficient to cause population declines necessitating reexamination of this management action. Quantifying aggregations and movements of channel catfish might allow managers to optimize the timing and location of removal efforts. We used active and passive radio telemetry to assess seasonal patterns in the distribution, aggregation, and movement of adults, and used temperature and activity sensors in some transmitters to identify behavior associated with channel catfish spawning which we corroborated through the back calculation of young-of-year otoliths to estimate hatch dates. We implanted 100 channel catfish in 2023 and 96 in 2024 with either a coded radio transmitter or a coded archive radio transmitter equipped with daily activity and temperature sensors. Tracking efforts occurred monthly outside of the spawning season and weekly during the expected spawning season (June-July) with raft-based tracking surveys. Despite a transmitter loss rate of 59% (n=116/196), we observed limited movement (< 5 river kilometers [rkm]) in spring/early summer followed by upstream movement in July in 2023 and May in 2024. Upstream movement coincided with warming water temperatures and largely occurred when the daily average water temperature reached 21°C, which is reported to initiate spawning for this species. Net movement was lower for fish < 440 mm TL (4.2 rkm) than for fish > 440 mm TL (14.4 rkm, p < 0.05). Linear mixed effects model results confirmed a positive relationship between movement rate and total length and a modal relationship between movement rate and a quadratic term for temperature with a predicted maximum movement rate identified at 22.1°C. Additionally, movement rate was 30.0% lower in 2024 compared to 2023 suggesting annual variability in movement patterns. Regression of activity as a function of temperature indicated that ten of twelve individuals displayed a modal activity pattern with predicted activity peaking in late-spring/early-summer at an average of 21.3°C. While our results do not suggest channel catfish have a propensity to aggregate, synchronized upstream movement likely cued by water temperatures near 21°C may provide the opportunity for resource managers to use passive sampling techniques to remove channel catfish during upstream spawning movements.
Keywords: Invasive species; Radio telemetry; Movement; Channel catfish; Spawning; San Juan River